Pengaruh Content Marketing dan Shopping Lifestyle terhadap Impulse Buying pada E-Commerce Lazada - Nathania Grace Edwin; Zumrotul Fitriyah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Indonesia’s internet user base is growing as a result of the swift progress of technolog, which also creates intense competition among e-commerce companies, including Lazada. Based on this phenomenon, the research aims to observe the influence of content marketing and shopping lifestyle on impulse buying behavior in Lazada e-commerce. A non-probability sampling method with purposive sampling is applied. The total sample, according to the predetermined criteria, was 98 respondents. Partial Least Square (PLS) is the data analysis technique used. The research findings show that content marketing does not affect impulsive buying in Lazada’s e-commerce. Conversely, impulsive buying in Lazada e-commerce is influenced by consumer shopping lifestyles.